HUBUNGAN KADAR HEMOGLOBIN IBU HAMIL DENGAN KEJADIAN STUNTING PADA BALITA DI PUSKESMAS NGEMPLAK - Setiyaningsih, Atik; Widyaning, Herdini; Wijayanti, Titik; Sri Ningsih, Magdalena (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2023)
One factor that can influence the occurrence of stunting in toddlers is the nutritional status of pregnant women. Nutrition for pregnant women is not only needed to meet the mother's own needs, but is also needed for the growth and development of the fetus in her womb. The nutritional problem that often occurs in pregnant women is anemia. The aim of this research is to analyze the relationship between Hb levels of pregnant women and the incidence of stunting in toddlers.The design of this research is correlation analytic with a cross sectional approach. The sampling technique used was total sampling with a sample size of 82 respondents. The results of data analysis using Chi-Square obtained a result of 0.000, p < 0.05, so the hypothesis was accepted, so there was a relationship between maternal Hb levels and the incidence of stunting at the Ngemplak Community Health Center. The Odds Ratio (OR) value is 8.337, meaning OR > 1 shows that the factor studied is a risk factor, so it can be concluded that anemia is a risk factor for stunting. Keywords: anemia, stunting, pregnancy, toddlers